A Statistical Study of the Subauroral Polarization Stream Over North American Sector Using the Millstone Hill Incoherent Scatter Radar 1979–2019 Measurements. Issue 10 (21st October 2020) - Aa, Ercha; Erickson, Philip J.; Zhang, Shun‐Rong; Zou, Shasha; Coster, Anthea J.; Goncharenko, Larisa P.; Foster, John C.
Abstract: This work conducts a statistical study of the subauroral polarization stream (SAPS) feature in the North American sector using Millstone Hill incoherent scatter radar measurements from 1979 to 2019, which provides a comprehensive SAPS climatology using a significantly larger database of radar observations than was used in seminal earlier works. Key features of SAPS and associated electron density ( N e ), ion temperature ( T i ), and electron temperature ( T e ) are investigated using a superposed epoch analysis method. The characteristics of these parameters are investigated with respect to magnetic local time, season, geomagnetic activity, solar activity, and interplanetary magnetic field (IMF) orientation, respectively. The main results are as follows: (1) Conditions for SAPS are more favorable for dusk than near midnight, for winter compared to summer, for active geomagnetic periods compared to quiet time, for solar minimum compared to solar maximum, and for IMF conditions with negative B y and negative B z . (2) SAPS is usually associated with a midlatitude trough of 15–20% depletion in the background density. The SAPS‐related trough is more pronounced in the postmidnight sector and near the equinoxes. (3) Subauroral ion and electron temperatures exhibit a 3–8% (50–120 K) enhancement in SAPS regions, which tend to have higher percentage enhancement during geomagnetically active periods and at midnight. Ion temperature enhancements are more favored during low solar activity periods, while the electron temperature enhancement remains almost constant as a function of the solar cycle. (4) The electron thermal content, T e × N e, in the SAPS associated region is strongly dependent on 1/ N e, with T e exhibiting a negative correlation with respect to N e . Key Points: Key features of North American SAPS and associated N e, T i, and T e were analyzed using four decade Millstone Hill IS radar measurements North American SAPS climatology in terms of MLT, season, geomagnetic activity, solar activity, and IMF condition was comprehensively studied Both ion and electron temperatures exhibit moderate enhancement around SAPS, with similar geomagnetic but different solar activity dependence